The Effect of Weeding Frequency on The Growth and Yield of Upright Beans on Ultisol Soil - Obel Obel; Meisilva Erona Sitepu; Fahrul Zaqi; Imelinda Imelinda (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2025)
Upright Beans (Phaseolus vulgaris. L) are one type of horticultural commodity that has great potential to be developed, but recently bean production has decreased. One of the causes is the presence of weeds that can cause competition in fighting for life's necessities. Therefore, control measures need to be taken by weeding. The purpose of this study was to determine the right weeding frequency to increase the growth and yield of upright bean plants. The study was arranged in a Randomized Block Design which was repeated 3 times. The research data were analyzed using the F test method at 5% level and followed by DMRT at 5% level. The results showed that the frequency of weeding at 21 HST gave the best results for plant height of 212.59 cm and the frequency of weeding carried out at 14 HST gave the best results for the parameters of the number of pods per plant of 14.90 and the weight of pods per plant of 129.63 g.